Customer Experience Analysis for Marketing Strategy Optimization Using CRAF Framework - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi, 2024)
This research explores the critical role of leveraging digital data and structured frameworks, specifically the Customer Review and Analysis Framework (CRAF), to optimize customer experience in the hospitality industry. Analyzing 1,028 guest reviews from Ayaka Suites Hotel reveals that 987 posts are positive, while only 40 are negative, indicating overall high satisfaction levels. The effectiveness of the Support Vector Machine (SVM) model for sentiment classification is demonstrated, achieving an accuracy of 94.99% without SMOTE and 89.22% with SMOTE. Furthermore, deploying the analysis results using Oracle APEX enables creating an interactive information system that provides real-time insights into customer feedback, facilitating dynamic data management and strategy adjustments. The findings underscore the importance of comprehensive feedback analysis for identifying improvement areas, enhancing service quality, and elevating guest satisfaction. The study concludes that adopting systematic frameworks like CRAF, advanced analytical models like SVM, and interactive deployment platforms like Oracle APEX is essential for achieving long-term success and maintaining high standards in service delivery within the hospitality sector.